Genotyping of Epstein-Barr virus in Brazilian Burkitt's lymphoma and reactive lymphoid tissue: Type A with a high prevalence of deletions within the latent membrane protein gene - Chen, Wen-Gang; Chen, Yuan-Yuan; Bacchi, Maura M.; Bacchi, Carlos E.; Alvarenga, Marcelo; Weiss, Lawrence M. (My University, 1996)
Both Epstein-Barr virus (EBV) types A and B are found in endemic Burkitt's lymphoma (BL) occurring in equatorial Africa. We studied 17 cases of Brazilian BL previously demonstrated to he EBV-positive to determine the EBV type as well as the presence of a characteristic 30 bp deletion within the 3' end of the latent membrane protein-1 (LMP-1) gene that may be important to the pathogenesis of several EBV-associated neoplasms. All cases in which the age was known were children. We found type A EBV in 13 of 14 (93%) evaluable cases, and type B in one case. The LMP-1 deletion was found in 12 of 15 (80%) evaluable cases, including the one case of type B EBV, and a similar high prevalence (59%) of the deletion was detected in EBV-positive normal and reactive lymphoid tissues from individuals from the same geographic region. The high proportion of cases associated with type A EBV suggests that immunodeficiency is not an important factor in the pathogenesis of Brazilian BL, in contrast to endemic African BL. The presence of the LMP-1 deletion in a high prevalence in the normal population in this region is unexplained.